TELAAH KRITIS ATAS LAPORAN KEUANGAN KOTA MADIUN - Kurrohman, Taufik (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
This research analysis the Madiun Cityâs financial reporting 2009. The author evaluate the development financial ability in Madiun City. The research object of this study is Madiun Cityâs Financial Report. The analysis development financial ability region is measured by budget and realize ratio. Finally, the result show that the realization of indirect expenditure in Madiun City is to low, the effects is some of people needed canât be fullfil by local government. Keywords: financial reporting, budgeting, realization.